Gambaran Diskriminasi Berbasis Gender di Amerika Serikat dalam On the Basis of Sex (2018) oleh Mimi Leder: sebagai sebuah Kajian Feminisme - Muhammad Ilham Nazilla; Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2021)
Gender-based discrimination is one of many kinds of discrimination ever existin this universe. It has been a crucial issue yet it is also often ignored by society. Thisphenomenon happens because patriarchy ideology has made it be a common thing insociety. The patriarchy ideology influences and makes people hegemonized inbehavior, way of life, and social structure. Related to this research, it mainly discussesthe depictions of gender-based discrimination in the U.S. which found in the movie‘On the Basis of Sex (2018)’ by Mimi Leder. The aim of this research is to find out thecauses, the depictions, and the ways the main character take actions to overcomegender-based discrimination in the U.S. according to the movie. This study iscategorized as a qualitative-based research that uses feminism approach as the appliedtheory. The research was done by doing analysis on the conversations over the scenesin the movie regarding to the research questions and applies the theory of feminism bySimone de Beauvoir (1949). The research found that depiction of gender-baseddiscrimination and men domination in the movie ‘On the Basis of Sex (2018)’ occursin the field of education, legal, working environment, and public place that was derivedfrom patriarchal culture in the United State for centuries. The discriminationexperienced by some characters both man and woman. Keywords: gender based discrimination, feminism, movie, patriarchy